2011
DOI: 10.1039/c0jm04242k
|View full text |Cite
|
Sign up to set email alerts
|

A novel concentration-gradient Li[Ni0.83Co0.07Mn0.10]O2 cathode material for high-energy lithium-ion batteries

Abstract: A novel concentration-gradient Li[Ni 0.83 Co 0.07 Mn 0.10 ]O 2 cathode material was successfully synthesized via co-precipitation, in which the core Li[Ni 0.9 Co 0.05 Mn 0.05 ]O 2 was encapsulated completely with a stable concentration-gradient layer having reduced Ni content. The electrochemical and thermal properties of the concentration-gradient Li[Ni 0.83 Co 0.07 Mn 0.10 ]O 2 were studied and compared to those of the core Li[Ni 0.9 Co 0.05 Mn 0.05 ]O 2 material alone. The concentration-gradient material ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 133 publications
(83 citation statements)
references
References 21 publications
2
81
0
Order By: Relevance
“…We also demonstrated that this structural mismatch could be mitigated by nano-engineering of the core-shell material, where the shell exhibits a concentration gradient [14][15][16] . However, because of the short shell thickness, the manganese concentration at the outer layer of the particle is low; therefore, its effectiveness in stabilizing the surface of the material is weak, especially during high-temperature cycling (55 • C).…”
mentioning
confidence: 95%
“…We also demonstrated that this structural mismatch could be mitigated by nano-engineering of the core-shell material, where the shell exhibits a concentration gradient [14][15][16] . However, because of the short shell thickness, the manganese concentration at the outer layer of the particle is low; therefore, its effectiveness in stabilizing the surface of the material is weak, especially during high-temperature cycling (55 • C).…”
mentioning
confidence: 95%
“…As with our previous CS [11][12][13][14][15] and CGCS powder [16][17][18] products which demonstrated superior cyclabilities, a harsh environment is required in order to distinguish electrode materials exhibiting improved performances. Therefore, the fabricated cells were cycled at a constant current of 20 mA g À1 (0.1 C rate, (Figure 8 c).…”
Section: Electrochemical Evaluation Of Cgcs Powders With Nanoparticlementioning
confidence: 99%
“…Intimate contact among the nanorods is likely to improve the resulting electric conductivity. [17,18] This structure also exhibited both a high capacity, due to the nickel-rich core, and good structural and thermal stability, due to the manganese-rich outer layers, and therefore, a long life.…”
Section: Introductionmentioning
confidence: 97%
“…The nickel-rich core delivers high reversible capacity, whereas the nickel-poor shell provides high thermal and cycling stability. Therefore, the NRC-CGS Li[NixCoyMn1-x-y]O2 materials exhibit promising electrochemical performance for LIBs [8,9]. However, due to the oxidation of nickel in the charging process, Ni 4+ is still present in the outermost surface of the NRC-CGS materials, which will react with the electrolyte, leading to undesirable capacity fading, especially at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%